Mixed attention ensemble for esophageal motility disorders classification. - Xiaofang Wu; Cunhan Guo; Junwu Lin; Zhenheng Lin; Qun Chen (PLoS ONE)
Esophageal motility disorders result from dysfunction of the lower esophageal sphincter and abnormalities in esophageal peristalsis, often presenting symptoms such as dysphagia, chest pain, or heartburn. High-resolution esophageal manometry currently serves as the primary diagnostic method for these disorders, but it has some shortcomings including technical complexity, high demands on diagnosticians, and time-consuming diagnostic process. Therefore, based on ensemble learning with a mixed voting mechanism and multi-dimensional attention enhancement mechanism, a classification model for esophageal motility disorders is proposed and named mixed attention ensemble(MAE) in this paper, which integrates four distinct base models, utilizing a multi-dimensional attention mechanism to extract important features and being weighted with a mixed voting mechanism. We conducted extensive experiments through exploring three different voting strategies and validating our approach on our proprietary dataset. The MAE model outperforms traditional voting ensembles on multiple metrics, achieving an accuracy of 98.48% while preserving a low parameter. The experimental results demonstrate the effectiveness of our method, providing valuable reference to pre-diagnosis for physicians.